2021
DOI: 10.1016/j.amsu.2021.102337
|View full text |Cite
|
Sign up to set email alerts
|

The predictors of depression and burnout among surgical residents: A cross-sectional study from Kuwait

Abstract: Background Surgical residency often poses a challenge to residents, with long working hours and a stressful work environment. Surgical residents are at an increased risk of burnout and depression. Such mental health burdens could go so far as to affect treatment outcomes. Aim To assess the prevalence and risk factors for depression and burnout among residents across surgical specialties in Kuwait. Materials and methods An online questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 45 publications
1
12
0
2
Order By: Relevance
“…While it remains unclear how students choose their specialty, as a Canadian study suggests [41], personal and professional factors may be the key to choosing a specialty, which leads to a more satisfying career and better care for their patients, as burnout correlates with lower levels of empathy, disengagement and career regret [42]. However, addressing burnout at all stages of medical training, either in medical school or residency is of critical importance for the quality of healthcare and the students' and residents' wellbeing [22,42,[52][53][54]. In terms of the presence of intentional shift in residency choice, one recent study [55] showed that in the USA, about one-fifth of surveyed medical students were preoccupied with changing their residency choice.…”
Section: Discussionmentioning
confidence: 99%
“…While it remains unclear how students choose their specialty, as a Canadian study suggests [41], personal and professional factors may be the key to choosing a specialty, which leads to a more satisfying career and better care for their patients, as burnout correlates with lower levels of empathy, disengagement and career regret [42]. However, addressing burnout at all stages of medical training, either in medical school or residency is of critical importance for the quality of healthcare and the students' and residents' wellbeing [22,42,[52][53][54]. In terms of the presence of intentional shift in residency choice, one recent study [55] showed that in the USA, about one-fifth of surveyed medical students were preoccupied with changing their residency choice.…”
Section: Discussionmentioning
confidence: 99%
“…The number of self-identified sources of stress were summed to produce a scale from 0 to 13. The median number of sources of stress in surgeons without any burnout was 5 [Interquartile Range 3-7], and in the burnout and severe burnout groups, it was 6 [3][4][5][6][7][8] and 7 [5-8.25], respectively (Kruskal-Wallis p-value = 0.002).…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, with the exception of one study on burnout among surgical residents (7), the prevalence of burnout and its associated factors among practicing physicians and, more specifically, surgeons, has not previously been reported in Kuwait. This study aims to assess the prevalence and associated factors of burnout among surgeons in Kuwait.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations